Técnicas de monitorização em redes ópticas de próxima geração - Sousa, Ana Oliveira de Pratas e (2014)
In this work several techniques to monitor the performance of optical networks were developed. These techniques are dedicated either to the measurement of the data signal parameters (optical signal to noise ratio and dispersion) or to the detection of physical failures on the network infrastructure. The optical signal to noise ratio of the transmitted signal was successfully monitored using methods based on the presence of Bragg gratings imprinted on high birefringent fibres that allowed the distinction of the signal from the noise due to its polarization properties. The monitoring of the signal group-velocity dispersion was also possible. In this case, a method based on the analysis of the electric spectrum of the signal was applied. It was experimentally demonstrated that this technique is applicable on both amplitude and phase modulated signals. It was also developed a technique to monitor the physical infrastructure of an optical access network. Once again, the application of Bragg gratings (this time imprinted on standard single mode fibres) was the basis of the developed method.